2010
DOI: 10.1038/sj.bjc.6605603
|View full text |Cite
|
Sign up to set email alerts
|

Flexible modeling improves assessment of prognostic value of C-reactive protein in advanced non-small cell lung cancer

Abstract: BACKGROUND: C-reactive protein (CRP) is gaining credibility as a prognostic factor in different cancers. Cox's proportional hazard (PH) model is usually used to assess prognostic factors. However, this model imposes a priori assumptions, which are rarely tested, that (1) the hazard ratio associated with each prognostic factor remains constant across the follow-up (PH assumption) and (2) the relationship between a continuous predictor and the logarithm of the mortality hazard is linear (linearity assumption). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…Patient information is obtained from systematic chart review, tumour board meetings, and patient interviews by specialized oncology data managers. This database has been used previously for research purposes [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Patient information is obtained from systematic chart review, tumour board meetings, and patient interviews by specialized oncology data managers. This database has been used previously for research purposes [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…For example, systemic inflammatory reaction indicators, such as elevation of serum C-reactive protein (CRP) and reduction in serum albumin, are reported as prognostic factors independent of stage in various solid cancers, including unresectable NSCLC (5)(6)(7)(8)(9). The Glasgow Prognostic Score (GPS), which is based on both albumin and CRP (10)(11)(12), is also a prognostic factor that is more effective than PS, even if treatment has been provided for unresectable NSCLC (10,11,13).…”
Section: Introductionmentioning
confidence: 98%
“…Third, cancer cells could increase the production of inflammatory cytokines, which could induce high CRP concentration in cancer patients 4. Many studies showed the elevation of pretreatment CRP to be a significant prognostic parameter in patients with esophageal cancer, 8-10 hepatocellular carcinoma,11 colorectal cancer,12-14 renal cell cancer,15-17 ovarian cancer,18 and non-small cell lung cancer (NSCLC) 19-23. Furthermore, we recently reported an association between preoperative serum CRP levels and pathologic parameter such as tumor size and lymphovascular invasion in patients with NSCLC 24…”
Section: Introductionmentioning
confidence: 99%